The role of Higher Education Institutions (HEIs) in encouraging entrepreneurial culture among students - Mohd Noor, Azura; Ahmad @ Muhammad, Norizam; Mohamad Fadzillah, Fazni (Faculty of Accountancy, 2024)
The field of entrepreneurship receives the attention of all stakeholders, especially the Ministry of Higher Education (KPT) to ensure that superior human capital that has strong entrepreneurial characteristics and can create jobs for others can be born in Higher Education Institutions (HEIs) according to the Malaysian Education Development Plan 2015-2025 (Higher Education) or PPPM (PT) 2015-2025. In 2021, it was found that a total of 93,352 students had ventured into entrepreneurial or business activities throughout their studies at HEI, which contributed to an increase of 35 percent compared to 68,937 students in 2020 (Kosmo, 10 September 2022). This shows that the field of entrepreneurship is gaining important foothold among higher education students during their study period.